2011
DOI: 10.1016/j.beproc.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity in a novel environment predicts both responding for a visual stimulus and self-administration of a low dose of methamphetamine in rats

Abstract: There is evidence that visual stimuli used to signal drug delivery in self-administration procedures have primary reinforcing properties, and that drugs of abuse enhance the reinforcing properties of such stimuli. Here, we explored the relationships between locomotor activity, responding for a visual stimulus, and self-administration of methamphetamine (METH). Rats were classified as high or low responders based on activity levels in a novel locomotor chamber and were subsequently tested for responding to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
65
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(81 citation statements)
references
References 53 publications
15
65
1
Order By: Relevance
“…By contrast, the tone cue appeared to elicit slightly greater responding during sucrose training. These findings are curious, but this difference could be due to the ability of psychostimulants to increase responding for visual stimuli (Caggiula et al, 2002;Deroche-Gamonet et al, 2002;Donny et al, 2003;Gancarz et al, 2011;Palmatier et al, 2006;Winterbauer and Balleine, 2007) and amplify sensitivity to acoustic stimuli (Davis, 1985;Davis et al, 1975), thereby enhancing the initial reinforcing and/or aversive properties of the light and tone cues, respectively (Baron and Kish, 1962). Regardless, our cue modality effects are consistent with the sensory reinforcement literature.…”
Section: Activation Of Action-outcome Habitssupporting
confidence: 84%
“…By contrast, the tone cue appeared to elicit slightly greater responding during sucrose training. These findings are curious, but this difference could be due to the ability of psychostimulants to increase responding for visual stimuli (Caggiula et al, 2002;Deroche-Gamonet et al, 2002;Donny et al, 2003;Gancarz et al, 2011;Palmatier et al, 2006;Winterbauer and Balleine, 2007) and amplify sensitivity to acoustic stimuli (Davis, 1985;Davis et al, 1975), thereby enhancing the initial reinforcing and/or aversive properties of the light and tone cues, respectively (Baron and Kish, 1962). Regardless, our cue modality effects are consistent with the sensory reinforcement literature.…”
Section: Activation Of Action-outcome Habitssupporting
confidence: 84%
“…Since the initial report by Piazza et al (1989), several studies have confirmed that HR rats show increased amphetamine-induced activity (Bevins et al, 1997) and amphetamine self-administration (Piazza et al, 1990(Piazza et al, , 2000Pierre and Vezina, 1997;Klebaur et al, 2001a;Cain et al, 2005Cain et al, , 2006Cain et al, , 2008 compared with LR rats. The differences between HR and LR rats in amphetamine self-administration are similar for both males and females (Klebaur et al, 2001a), and these individual differences generalize to other stimulant drugs, including cocaine (Mantsch et al, 2001;Sell et al, 2005;Kabbaj, 2006;Belin et al, 2008Belin et al, , 2011Walker et al, 2009) and methamphetamine (Bevins and Peterson, 2004;Gancarz et al, 2011). Nicotine self-administration also is greater in HR rats than in LR rats (Suto et al, 2001), although these individual differences may not occur in nicotine-induced hyperactivity .…”
Section: Preclinical Behavioral Neuropharmacologymentioning
confidence: 92%
“…For example, maintenance of amphetamine self-administration is disrupted by novel stimuli, and this disruption is greater in HR rats than it is in LR rats (Cain et al, 2004). HR rats also show more responding than LR rats to earn novel visual stimuli (cue light illumination; Gancarz et al, 2011). These latter results are important because drug self-administration studies often use cue light illumination to signal the drug infusion or a time-out period (no drug availability) after the infusion.…”
Section: Preclinical Behavioral Neuropharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the study experiments, animals were provided adaptive feeding for 7 days. A previous study suggested that there were individual differences in the initial locomotor response to a novel environment in rats (28). Therefore, the adaptive feeding may make rats familiar with the test environment in advance and avoid the effect of a novel environment on locomotor activity.…”
Section: Animalsmentioning
confidence: 99%